Fenomenologi Imaji dalam Seni: Sebuah Pergeseran Peran Subjek menuju Saksi - Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2017)
Art seems to always deal with subjects, both the artist and the spectator. The awareness that an image is not a concept may provoke those doing and experiencing art to reposition themselves as appreciators of the image. This article shifts the focus from concept to image. Art event is a sort of lectio imaginem, an experience of reading and not merely interpreting the image. Each artwork is transcendent, since every time it will speak differently when reencountered. Yet it might even frightfully reinterpret the audience differently, recreating the identity as a different figure in its eyes. Phenomenologically, the spectators are looked upon by the image through the works of art. The subject is assessed and transformed from I into me, that it becomes a witness in the presence of an image revealing itself. This article is an invitation to maintain the equilibrium between critical and appreciative atitudes, between theory and image, within the world of art. All individuals, without exception, are assessed by art. Perhaps they only need to forbear, to let themselves deluged in the surface, to become the witnesses fascinated before and moved by the saturation of the image.